1979
DOI: 10.1002/app.1979.070231007
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic mechanical properties of oil-extended, carbon black-reinforced, and peroxide-crosslinked EPDM rubber

Abstract: SynopsisThe effects of aromatic, naphthenic, and paraffinic oils on the dynamic mechanical behavior of an EPDM rubber (Nordel 1560) have been investigated as have the influences of oil level, carbon black loading, and peroxide crosslinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This shows that EPDM/NBR is cross-linked and the interaction between the EPDM/NBR and the iPP has increased. Hourston and Byrne [30,31] investigated that the dynamic mechanical behavior of EPDM and reported that the tan δ max is increased by cross-linking which is shown with the decrease of the degree of crystallinity from 41.65 to 23.75 as the loading of EPDM/NBR content increases from 0 to 40 wt. % in the blend.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 96%
“…This shows that EPDM/NBR is cross-linked and the interaction between the EPDM/NBR and the iPP has increased. Hourston and Byrne [30,31] investigated that the dynamic mechanical behavior of EPDM and reported that the tan δ max is increased by cross-linking which is shown with the decrease of the degree of crystallinity from 41.65 to 23.75 as the loading of EPDM/NBR content increases from 0 to 40 wt. % in the blend.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 96%
“…This indicates that the EPDM is crosslinked and the interaction between the EPDM and the PP has increased. Byrne and Hourston9, 10 investigated the dynamic mechanical behavior of EPDM and reported that the tan max is increased by crosslinking, which is ascribed to the decrease of the degree of crystallinity from 41.63 to 23.73 as the EPDM content increases from 0 to 40 wt % in the blend. The same phenomenon was observed by Coran and Patel 11.…”
Section: Resultsmentioning
confidence: 99%
“…Rinde and Hoge8, 9 constructed the master curve of dynamic shear modulus of polystyrene bead foams and solid polymer for different frequencies as well as for a wide range of temperatures. The linear elastic properties of microcellular plastics have been reported by Jackson et al10 Strain‐dependent dynamic mechanical properties of solid rubbers are reported by several workers,11–20 whereas very little work on closed cell microcellular rubbers has been investigated. The studies on the viscoelastic behaviors of closed cell microcellular ethylene–octene copolymer21–23 show that the storage modulus and tan δ (the ratio of loss modulus and storage modulus) are frequency‐ and temperature‐dependent, and the log of storage modulus bears a linear relationship with the log of density.…”
Section: Introductionmentioning
confidence: 94%